IDDF2018-ABS-0167 The TCF3/MIR-145–5P/LINC00113 positive feedback loop promotes colorectal cancer progression by silencing STAT1. (June 2018) - Yan, Changsheng
Abstract : Background: To identify the role of LINC00113 in colorectal cancer. Methods: Jaspar and Cor R package was used to predict the potential translational factor of LINC00113. CHIP and dual luciferase report assay were enrolled to confirm the binding sites between LINC00113 and translational factor. Besides, dual luciferase report assay was used to confirm the binding site of LINC00113, miRNA and TCF3. Flow cytometry was used to detect the cell cycle and apoptosis. RIP assay was used to confirm the binding of LINC00113 and DNMT1. Results: Using the Gene expression omibus (GEO) data set and bioinformatics analyses, we identified LINC00113 as an independent risk prognostic factor in colorectal cancer. To identify the mechanism how LINC00113 in colorectal cancer, we firstly to seek the translational factor which could up-regulate the expression of LINC00113. We found that the expression level of TCF3 was strongly positively correlated with LINC0113. Besides, knockdown and overexpress of TCF3 could coordinately lead to the alteration of LINC00113. What's more, CHIP and luciferase assay confirm that TCF3 binds to the promoter sequence of LINC00113 and thus promoting the expression of LINC00113. Then we found that LINC00113 might be a negative regulator of miR-145–5 p by loss- and gain-of-function assay. Besides, we found that miR-149–5 p had the potential ability binding to the 3'-UTR of TCF3, thus leading to the degradation of TCF3. However, as the increased level of LINC00113, the expression level of miR-145–5 p was lowly expressed in colorectal cancer, which leads to the expression level of TCF3 significantly up-regulated in colorectal cancer. At last, the high level of TCF3 in turn promotes the expression of LINC00113. Moreover, we also found that LINC00113 could bind to DNMT1 to promote the methylation of promoter sequence of STAT1 and leading to the down-regulation of STAT1, which act as a tumour suppressor in colorectal cancer. Conclusions: Our studies uncover a mechanism for constitutive LINC00113/miR-144–5 p/TCF3 feedback loop activation in colorectal cancer. Besides, high expressed of LINC00113 resulted in the down-regulation of STAT1, which further promoted the progression of colorectal cancer.